The Influence of Dynamic Capability and Collaboration Strategy on the Company Positional Advantage: (A Study of Airports in Indonesia) - Ferdian Agustiana, Dyah Budiastuti (International Journal of Advanced Science and Technology, 2020)
The service performance of several airports under the auspices of Angkasa Pura is on par with other world class airports. It is important to create a company positional advantage for airports in Indonesia. But there are still facts about the problem with this. In this regard, the purpose of this study is to examine the effect of dynamic capability and collaboration strategy on company position advantages in the airport industry in Indonesia. The research design is quantitative research approaches. The type of research used in this study is verification. The survey method applied is an explanatory survey. The unit analysis in this study is airports in Indonesia. The observation unit is the airport management in Indonesia. The research data collected was in the time span of cross section / one shoot. The population in this study is all airports in Indonesia. Samples is taken as many as 50 airports. Analysis of causality in this study using Partial Least Square. The results of study reveals that the company position positional advantage is more dominantly formed by collaboration strategy and supported by dynamic capability. The results of this study have implications for airport management that the development of company position advantages can be carried out by developing collaboration strategies, especially in terms of cooperation with institutions, followed by cooperation with logistics and transportation vectors, regional airports, private stakeholders, airlines, and tour operators. These efforts are supported by the development of dynamic capability, which prioritizes to the aspects of reconfiguration strategy, seizing capacity and sensing capability.